2007
DOI: 10.1590/s1676-06032007000200016
|View full text |Cite
|
Sign up to set email alerts
|

Uso de fragmentos florestais por anuros (Amphibia) de área aberta na região noroeste do Estado de São Paulo

Abstract: Landscape arrangement plays a key role in community structure and composition. Our study was based on the hypothesis that forest fragments work as shelter areas for open-area anuran species. Four forest fragments were studied in the municipality of Icém, northwestern São Paulo State; the fragments were 1 to 4 km apart from each other. The anurans were sampled in the fragments by pitfalls, artificial shelters, and active search. Twelve species were registered (48% of the species known for the region); three of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 26 publications
1
8
0
4
Order By: Relevance
“…In forests, the richness and composition of vegetation, elevation, structure and depth of leaf-litter, and proximity to ponds are some factors that may influence richness, abundance, and composition of anuran assemblages (Paris and McCarthy 1999, Willians and Hero 2001, Peltzer et al 2003, Van Sluys et al 2007). However, in the present study, the structure found in the forest seems to be a consequence of an opportunist occurrence to foraging and maintenance of temperature and body moisture, as observed for anurans in fragments of Semideciduous Forest (Silva and Rossa-Feres 2007).…”
Section: Discussionsupporting
confidence: 45%
“…In forests, the richness and composition of vegetation, elevation, structure and depth of leaf-litter, and proximity to ponds are some factors that may influence richness, abundance, and composition of anuran assemblages (Paris and McCarthy 1999, Willians and Hero 2001, Peltzer et al 2003, Van Sluys et al 2007). However, in the present study, the structure found in the forest seems to be a consequence of an opportunist occurrence to foraging and maintenance of temperature and body moisture, as observed for anurans in fragments of Semideciduous Forest (Silva and Rossa-Feres 2007).…”
Section: Discussionsupporting
confidence: 45%
“…O registro de um elevado número de espécies que se reproduzem pelo modo do tipo 1 também foi observado para outras regiões da Floresta Atlântica, por exemplo: 50% na Serra do Japi (Haddad & Sazima 1992), 50% no Parque Estadual de Intervales (Bertoluci 2001), 50% no Parque Estadual Mata dos Godoy , 52,6% na Fazenda São Luis, Ribeirão Branco/Apiaí (Pombal Jr. & Haddad 2005), 52% na Floresta Estadual Edmundo Navarro de Andrade, Rio Claro (Toledo et al 2003), 54% em Tijucas do Sul (Conte & Machado 2005), 55% na Fazenda Gralha Azul, Fazenda Rio Grande (Conte & Rossa-Feres 2007) e 52% na Mata São José, Rio Claro (Zina et al 2007). Em locais que apresentam sazonalidade acentuada e paisagem extremamente antropizada tendem a apresentar um maior número de espécies com este modo reprodutivo, como por exemplo: 64% em Guararapes (Bernarde & Kokubum 1999), 59% em Nova Itapirema (Vasconcelos & Rossa-Feres 2005), 60% em Santa Fé do Sul, (Santos et al 2007) e 64% em Icém (Silva & Rossa-Feres 2007). Segundo Hödl (1990), fatores ambientais, como a alta umidade e temperatura, além de ausência de sazonalidade são importantes para evolução de modos reprodutivos especializados.…”
Section: Composição Uso Do Habitat E Modos Reprodutivosunclassified
“…Portanto podese considerar que fragmentos, mesmo alterados, são de relevada importância para conservação de anfíbios, pois além de suprir as necessidades de espécies que se reproduzem em ambientes florestados (Santos & Conte, 2014), também são usados por espécies que reproduzem em área aberta. Estes ambientes disponibilizam os recursos essenciais para a manutenção das populações de anfíbios anuros já que estes podem ser usados, por exemplo, como corredores de dispersão (Stebbins & Cohen, 1995), para atividades de forrageio e áreas de refúgio, tanto para adultos quanto para jovens (Silva & Rossa-Feres, 2007;Silva et al, 2011).…”
Section: Discussionunclassified